2023
DOI: 10.1111/cas.15964
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood inflammatory biomarkers dynamics reflect treatment response and predict prognosis in non‐small cell lung cancer patients with neoadjuvant immunotherapy

Qilin Huai,
Chenyu Luo,
Peng Song
et al.

Abstract: Neoadjuvant immunotherapy has significantly changed the therapeutic approach for treating patients with surgically resectable non‐small cell lung cancer (NSCLC). Here, peripheral blood inflammation‐based biomarkers as well as previously less focused eosinophil fraction, modified Glasgow prognostic score (mGPS), and prognostic nutritional index (PNI) were systematically included to comprehensively analyze their potential in predicting neoadjuvant immunotherapy efficacy and prognosis. We enrolled 189 patients (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated that multiple factors were associated with MPR achievement after NCIO, including peripheral blood inflammatory biomarkers, 18fluorine-fluorodeoxyglucose uptake, PD-L1 expression, tumor mutational burden, and tumor regression rate (37)(38)(39)(40). Our study analyzed general clinical and laboratory characteristics and found that LY, tumor burden, N classification, radiographic response, pulmonary atelectasis, and pre-treatment PD-L1 expression level were independent factors affecting MPR rate.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have indicated that multiple factors were associated with MPR achievement after NCIO, including peripheral blood inflammatory biomarkers, 18fluorine-fluorodeoxyglucose uptake, PD-L1 expression, tumor mutational burden, and tumor regression rate (37)(38)(39)(40). Our study analyzed general clinical and laboratory characteristics and found that LY, tumor burden, N classification, radiographic response, pulmonary atelectasis, and pre-treatment PD-L1 expression level were independent factors affecting MPR rate.…”
Section: Discussionmentioning
confidence: 62%
“…Rampant inflammation and malnutrition play pivotal roles in cancer patients, resulting in poor treatment outcomes [29]. Mounting evidence demonstrates the utility of peripheral blood-based parameters as surrogate markers reflecting the inflammatory state and nutritional condition of cancer patients [30,31]. The minimally invasive retrieval, low cost, and quantitative nature of complete blood count (CBC)-derived biomarkers render them particularly advantageous for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the already mentioned potential role of lactate dehydrogenase levels, other clinical and peripheral blood inflammation-based biomarkers have also been studied in this subject. A prospective observational trial found that high absolute lymphocyte count and absence of liver metastases were associated with durable clinical benefit of ICI in NSCLC [81]. An additional study suggested that high baseline levels of transcription factor T cell factor 1 (TCF1+) CD 8 + T cell ratio and peripheral white blood cell count, lymphocyte percentage and cytokeratin 19 fragment after one cycle of ICI treatment may predict treatment response [82].…”
Section: Predictive Biomarkers Of Ici Response In Nsclcmentioning
confidence: 99%
“…An additional study suggested that high baseline levels of transcription factor T cell factor 1 (TCF1+) CD 8 + T cell ratio and peripheral white blood cell count, lymphocyte percentage and cytokeratin 19 fragment after one cycle of ICI treatment may predict treatment response [82]. Finally, post-treatment eosinophil fraction, systemic immune-inflammation index, modified Glasgow prognostic score, and systemic immuneinflammation index variation were also mentioned as independent predictors of major pathologic response in patients with NSCLC treated with neoadjuvant ICI [81].…”
Section: Predictive Biomarkers Of Ici Response In Nsclcmentioning
confidence: 99%